Case report: Hepatic inflammatory pseudotumor-like follicular dendritic cell sarcoma: A rare case and minireview of the literature - Ding, Fan; Wang, Chao; Xu, Chi; Tang, Hui (Frontiers in Medicine, 2022)
Inflammatory pseudotumor (IPT)-like follicular dendritic cell sarcoma (FDCS) is a rare neoplasm referred to as the FDCS variant. Here we report a 66-year-old female patient suffering from hepatic IPT-like FDCS and summarize IPT-like FDCS reported in the literature. The patient presented with obvious abdominal pain without significant laboratory abnormalities and subsequently underwent surgical resection of a hepatic lesion. Postoperative pathological results demonstrated a vascular tissue-rich neoplasm (7.0-cm maximum diameter). The tumor cells expressed CD21 and CD35, and in situ hybridization detected Epstein–Barr virus-encoded RNA (EBER). Metastasis or recurrence was not detected during the 7-year follow-up.